DETECTIVES WITH PIMPLES: HOW «TEEN NOIR» IS CROSSING THE FRONTIERS OF THE TRADITIONAL NOIR FILMS - Mancelos, João de (2019)
In the last ten years, teen noir movies and series — such as Donnie Darko (2001), Brick (2005), or Veronica Mars (2004-2007) — have become increasingly popular among audiences, both in the USA and in Europe, and aroused the curiosity of critics. These teen noir adventures present darker themes and technical features that distinguish them from numerous productions aiming at young adults. Their narrative and aesthetic characteristics reinvent and subvert the tradition of classic noir movies of the forties and fifties, thus generating a sense of novelty. In this article, I focus my attention on Veronica Mars, a famous teen noir series, created by Rob Thomas, to examine: a) the teen noir themes; b) the new profile and role of the private investigator; c) the empowerment of girls/young women; d) razor-sharp dialogues; e) intertextual references to oldschool noir movies. In order to do so, resort to the research of specialists in the field of neo noir, such as Mark Conrad, Foster Hirsch, or Roz Kaveney. My main goal is to prove that a new (sub)genre is slowly emerging and revivifying teen cinema.